THE INFLUENCE OF DIFFERENCES IN FIVE LEARNING STYLES ON EXAMINATION ANXIETY AMONG STUDENTS AT MUHAMMADIYAH SAINTEK UNIVERSITY - Suyanto; Fisa Wisnu Wijaya; Purwanto; Nurkomar Hidaya; Warno (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This quantitative study aims to compare pre-examination anxiety levels among 46 university students from various higher education institutions based on five learning style categories (Visual, Auditory, Writing, Kinesthetic, and Social). Data were collected through questionnaires and analyzed using a One-Way ANOVA. The assumption tests indicated that the data were normally distributed (Shapiro–Wilk, p = 0.092) and that variances across groups were homogeneous (Levene’s Test, p = 0.791), thereby meeting the requirements for parametric analysis. The main analysis revealed no significant differences in anxiety levels among students with the five learning styles (F(4,41) = 1.954; p = 0.120 > 0.05). Further analysis using the Tukey HSD post hoc test also confirmed the absence of significant differences across all group pairs. These findings indicate that dominant learning styles do not significantly influence students’ academic anxiety responses prior to examinations. The results suggest that educators should continue to implement varied instructional strategies and foster supportive learning environments to help all students effectively manage emotional pressure during examination periods.